Testing the Transparency Implications of Mandatory IFRS Adoption: The Spread/Maturity Relation of Credit Default Swaps - Bhat, Gauri; Callen, Jeffrey L.; Segal, Dan (Management Science, 2016)
This study tests whether international financial reporting standards (IFRS) adoption increased accounting transparency based on model-driven hypotheses. Duffie and Lando [Duffie D, Lando D (2001) Term structures of credit spreads with incomplete accounting information. Econometrica 69(3):633–644] show that changes to accounting transparency affect the spread/maturity relation of credit default swap (CDS) instruments in very specific ways. Consistent with their model, we find that CDS spreads are lower across maturities following the adoption of IFRS, and the slope and concavity of the CDS spread/maturity relation are higher. These changes did not occur to the spread/maturity relation of a control sample of CDS instruments. Predicted changes apply more intensely to firms with low pre-IFRS transparency. Overall, this study provides strong evidence that IFRS adoption increased accounting transparency. This paper was accepted by Mary Barth, accounting.